2009
DOI: 10.1038/ijo.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor is a regulator of orphan nuclear receptor NOR-1 gene transcription in adipocytes

Abstract: Objective: The liver X receptors (LXRs) are ligand-activated nuclear transcription factors that have been shown to play major roles in lipid, glucose and cholesterol metabolism. Recently, members of the NR4A orphan nuclear receptor family have also been shown to regulate the expression of important genes in metabolically active tissues such as liver, adipose and skeletal muscle. Here, we investigated the role of LXRs to regulate the expression of the nuclear receptor NOR-1 (neuron-derived orphan receptor-1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…3f ). We therefore investigated the hypothesis that DDA could modulate the liver-X-receptors (LXRs) as DDA-induced events such as triacylglycerol synthesis 5 , 9 and NOR1 expression are also known to be regulated by the LXRs 27 . We found that DDA inhibited LXR-dependent luciferase activity stimulated by 22(R)-hydroxycholesterol (22(R)HC) in the presence of LXRα or LXRβ in a concentration-dependent manner, with IC 50 values of 362 ± 52 and 76 ± 12 nM, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3f ). We therefore investigated the hypothesis that DDA could modulate the liver-X-receptors (LXRs) as DDA-induced events such as triacylglycerol synthesis 5 , 9 and NOR1 expression are also known to be regulated by the LXRs 27 . We found that DDA inhibited LXR-dependent luciferase activity stimulated by 22(R)-hydroxycholesterol (22(R)HC) in the presence of LXRα or LXRβ in a concentration-dependent manner, with IC 50 values of 362 ± 52 and 76 ± 12 nM, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of NOR‐1 in macrophages reduces the synthesis of inflammatory cytokines and chemokines (van Tiel & de Vries, 2012). A previous study discovered that LXRs and NOR‐1 have an interdependent regulatory association and LXRs are a regulator of NOR‐1 gene transcription in adipocytes (Kumar et al, 2009). Subsequent research also uncovered that LXRα activation elevates NOR‐1 expression in Kupffer cells, which in turn upregulates cytokines (including TNF‐α and IL‐10) to resist LPS‐induced inflammation (K. He et al, 2015).…”
Section: Downstream Targets Of Lxrα In the Regulation Of Inflammationmentioning
confidence: 99%
“…LINC00473 has been reported to interact with NONO, a protein that interacts with cyclic AMP-responsive-element-binding protein (CREB) -regulated transcription coactivator (CRCT), which is essential in CREB transcriptional regulation (Chen et al, 2016). CREB directly and through interaction with NR4A3, (Cannon and Nedergaard, 2004;Kozak et al, 1994;Yubero et al, 1998;Yubero et al, 1994 ), activates the UCP1 promoter (Kumar et al, 2008;Myers et al, 2009;Pearen and Muscat, 2010). It is possible that LINC00473 may coordinate the actions of transcription factors that regulate the UCP1 promoter.…”
Section: Discussionmentioning
confidence: 99%